Serum soluble alpha-klotho klotho and cognitive functioning in older adults aged 60 and 79: an analysis of cross-sectional data of the National Health and Nutrition Examination Survey 2011 to 2014 - Song Ge; Fanghong Dong; Chong Tian; Chih-Hsiang Yang; Minhui Liu; Jingkai Wei (BMC Geriatrics, 2024)
Abstract Objectives Klotho, consisting of membrane klotho and soluble alpha-klotho, is found to be associated with better cognitive outcomes in small samples of the aged population. We aimed to examine the association of serum soluble alpha-klotho with cognitive functioning among older adults using a nationally representative sample of U.S. older adults. Method A total of 2,173 U.S. older adults aged 60–79 years in the National Health and Nutrition Examination Survey from 2011 to 2014 were included in this cross-sectional analysis. Serum soluble alpha-klotho was measured in the laboratory and analyzed with an ELISA kit. Cognitive function was measured using the Consortium to Establish a Registry for Alzheimer’s Disease Word Learning subtest (CERAD-WL) immediate and delayed memory, the Animal fluency test (AFT), and the Digit Symbol Substitution Test (DSST). Test-specific and global cognition z-scores were calculated based on sample means and standard deviations. Multivariable linear regression models were applied to examine the association of quartiles and continuous value of serum soluble alpha-klotho with test-specific and global cognition z-scores. Subgroup analysis was conducted by sex. The following covariates were included in the analysis- age, sex, race/ethnicity, education, depressive symptoms, smoking status, body mass index (BMI), physical activity, stroke, prevalent coronary heart disease, total cholesterol, and systolic blood pressure. All the information was self-reported or obtained from health exams. Results Serum soluble alpha-klotho level in the lowest quartile was associated with lower z-scores for DSST (beta [β] =-0.13, 95% confidence interval [CI]: -0.25, -0.01). For subgroup analysis, serum soluble alpha-klotho level in the lowest quartile was associated with lower z-scores for DSST (β=-0.16, 95% CI: -0.32, -0.003) and global cognition (β=-0.14, 95% CI: -0.28, -0.01) among female participants. No association was found between continuous serum soluble alpha-klotho and cognitive functioning among the participants. Conclusions Lower serum soluble alpha-klotho quartile was associated with poorer cognitive functioning among older women. Future studies are expected to examine the longitudinal association between klotho levels and cognitive outcomes.